Optimalisasi Perjalanan Dinas Badan Perencanaan Pembangunan Daerah Garut dengan Aplikasi Web Inovatif - Supriatna, Asep Deddy; Satria, Eri; Handayani, Nanda (Jurnal Algoritma, 2024)
An Official Travel Order is a document of official travel assignments for government officials. Initially, the Garut Regional Development Planning Agency made official travel orders manually with the risk of errors and taking longer in the process. This causes accessibility issues, approval delays, as well as poorly organized records and report management issues. The solution is to build an application for the department to manage official travel which aims to improve the control and management of official travel, including validation of assignment orders, management of official travel orders, employee data, finances including accommodation costs, as well as uploading proof of implementation of official travel for monitoring travel status. . Application design applies the Rational Unified Process methodology which covers the inception, elaboration, construction and transition stages. The modeling involves Unified Modeling Language modeling. The result of this research is a Web-Based Official Travel Control Application at the Garut Regional Development Planning Agency which can help in the productivity of government administration by automating processes so that it can reduce the time and effort needed to administer and manage manual administration.